Legal Liability in Sharia Fintech: A Study of Default in Peer-to-Peer Lending Schemes - Faradilla Kurnia Asyifa; Diandra Nazira Anshar; Baidhowi Baidhowi (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal liability of Sharia fintech providers in peer-to-peer lending schemes, focusing on default risks within the framework of Indonesian financial regulations and Islamic legal principles. Using a normative juridical approach, the research analyzes statutory provisions, doctrinal theories, and Sharia principles governing financial transactions. The findings reveal that fintech providers cannot be positioned merely as passive intermediaries, as regulatory frameworks such as POJK No. 10/POJK.05/2022 and the Consumer Protection Law impose professional obligations related to risk management, transparency, and accountability. The persistence of standard clauses transferring all risks to lenders demonstrates a structural imbalance that contradicts both positive law and Sharia principles, particularly those emphasizing justice, trust, and proportional risk sharing. Default is therefore not solely a business risk but may generate legal consequences when negligence is identified. This study proposes a reconstruction of liability through the integration of kafalah and takaful mechanisms alongside a risk-based liability approach, offering a more balanced and ethically grounded model of protection for lenders in Sharia fintech ecosystems.